Karya Sastra Jepang dalam "Zeitgeist" Sejarah - Surajaya, I Ketut (Wacana, Journal of the Humanities of Indonesia, 2002)
This article explores the relationship between literature and the history of Japanese society. The study shows that many literary works reflect the dynamics of culture, economics, ideology, and thoughts in Japanese society. Based on the, the writer believes that those literary works are useful to understand the spirit of age (Zeitgeist) in Japanese history. The writer also deals with the issues of globalis which play important part in Japanese literary discourse, particularly in multiculturalism theme.